Pendampingan digital branding bagi UMKM melalui program magang mahasiswa di Dinas Perdagangan Provinsi NTB - Cahyaningrum, Dinis; Wahyulina, Sri; Fauzi, Armi Sulthon; Mutia, Ainaya; Oktavia, Salsabila Rahma; Khofia, Kinayatul; Wahyudin, Ilham; Gazali, Imam (Nur Science Institute, 2025)
This community service program aimed to enhance the digital branding capacity of MSMEs through a student internship program in collaboration with the Department of Trade of West Nusa Tenggara Province. Two partner MSMEs, Goyang Lidah and Waroh, were assisted in developing visual content (product photos and promotional videos) and optimizing their social media presence. The method consisted of initial observation, practical training, direct mentoring, and evaluation. Results showed a significant improvement in online promotional activities: Waroh’s engagement rate increased from 1.39% to 2.47%, and sales rose by 12%. Goyang Lidah saw an increase in engagement from 0.10% to 0.16%, accompanied by a 4% rise in sales. The program also strengthened participants’ digital marketing skills by applying theoretical knowledge in real-world contexts. This collaboration between higher education institutions, MSMEs, and local government proved effective in promoting grassroots digital transformation. It is recommended that future programs expand to involve more MSMEs and incorporate a broader range of digital marketing strategies.